Politik Hukum Pembuktian dalam Penyelesaian Sengketa Konsumen di Indonesia - Syam, Misnar (UNES Law Review, 2023)
Guidelines (GBHN) of Indonesia, including through the Decree of the People's Consultative Assembly (TAP MPR) No. II of 1988. Consumer protection is regulated by Law No. 8 of 1999 concerning Consumer Protection. Repressive protection is an effort to restore the losses suffered by consumers. In any consumer dispute resolution process, evidence is required. Under the Consumer Protection Law (UUPK), the burden of proof is shifted, as stipulated in Articles 19, 22, 23, and 28, where the burden of proof falls on the business entity obligated to prove its innocence. Evidence in civil procedure law is regulated in Article 163 of the HIR/283 RBg, following the ordinary burden of proof. This leads to a lack of harmony in the regulations, which can result in confusion and legal uncertainty in its implementation. This can hinder the achievement of the goals of consumer protection. Legal policy is the direction of future legal regulations, so when making laws, it is necessary to refer to Indonesia's legal policy. Based on the above reasons, the research problem in this study is how evidence is handled in the resolution of consumer disputes from the perspective of Indonesian legal policy. The research method used is normative. In conclusion, in the legal policy of consumer protection, especially in the dispute resolution process, there is a need for harmonization between the Consumer Protection Law (UUPK) and future civil procedural law to ensure legal certainty.